Proteasome inhibitors in medullary thyroid carcinoma: time to restart with clinical trials? - Fanciulli, Giuseppe; Modica, Roberta; La Salvia, Anna; Grossrubatscher, Erika Maria; Florio, Tullio; Ferraù, Francesco; Veresani, Alessandro; Russo, Flaminia; Colao, Annamaria; Faggiano, Antongiulio (Frontiers in Endocrinology, 2023)
Introduction: Medullary thyroid cancer (MTC) is a rare thyroid tumor whose management in advanced stages is challenging, despite therapeutic options have expanded in recent years. Proteasome inhibitors (PrIn) have shown the ability to improve patient outcomes, including survival and quality of life, in several malignancies, due to their ability to impair cell proliferation and cause apoptosis through the inhibition of the proteasome activity. Consequently, these drugs could represent a useful tool, alone or in combination, in MTC patients. Aim of the study: This review aims to summarize the available in vitro and in vivo data about the role of PrIn in MTC. Material and Methods: We performed an extensive search for relevant data sources, including full-published articles in international online databases (PubMed, Web of Science, Scopus), preliminary reports in selected international meeting abstract repositories, and short articles published as supplements of international meetings, by using the following terms: medullary thyroid carcinoma, proteasome inhibitors, bortezomib, carfilzomib, ixazomib, delanzomib, marizomib, oprozomib, and MG132. Additionally, we conducted with the same keywords, an in-depth search in registered clinical trials repositories. Results: Our search revealed in vitro studies in human and murine MTC cell lines, based on the use of PrIns, both alone and in combination with other anticancer drugs, and two pertinent clinical trials. Conclusions: We found a strong discrepancy between the clear evidence of PrIns effects in preclinical studies, and the scarcity/early interruption of clinical trials. We might speculate that difficulties in enrolling patients, as happens in other rare diseases, may have discouraged trials implementation in favor of drugs already approved for MTC. However, given the concrete improvement in the comprehension of the molecular basis of PrIn effects in MTC, new clinical trials are warranted: their use, alone or in combination with other anticancer agents, could indeed represent an option to enhance therapeutic response, and to ultimately improve patient’s outcome and survival.